The contributions of the muslim Arabs to the development of science (2014)
There are two laws in the course of human existence that Physical Science briefly termed as science, otherwise called law of gravity and divine laws designed to govern the conduct of man. Unlike the physical laws, divine laws from Islamic point of view are not implemented under compulsion (Q. 2:256). The laws of Islam are, in fact, the scientific laws of human nature. Man is however influenced by his environment which may lead to his deviation from the tendencies of his nature and the right path of Islam. To teach man his natural duties, prophets were sent by God periodically. Thus, while physical laws can be discovered by experience, Islamic laws are revealed to the prophets by God for transmission to human beings. Man is honoured by virtue of knowledge over and above other creatures and this made him the vicegerent of Allah to execute the divine laws on earth. Man is endowed with particular faculties of mind to enable him discover the physical laws, and to harness all the resources of the earthly life to his best advantage. The fact that everything has been made subservient to man is a great incentive that provided for easy exploitation of all resources for the welfare of mankind. He, however, needs to acquire the knowledge of both physical science and divine laws for him to make appropriate utilisation of the earthly resources. That is why Islam has declared acquisition of knowledge as compulsory for all Muslims'. It is this mantra that propelled Muslims to want to actualize an orderly human civilisation based on unity devoid of racial, ethnic and religious discrimination This fact is in their quest to learn from earlier civilisatioris and also to incorporate their science and culture. Though the study of various aspects of sciences and arts that flourished in the apogee of their civilisation might not have been standardised, it, however, brought development and honour to humanity. They contributed to subjects like Mathematics, Physics. Medicine, Astronomy, Chemistry, Geography and Agriculture among others in arts and sciences.